Self‐Assembly of n‐Alkyl‐ and Aryl‐Side Chain Ureas and Their Derivatives as Evidenced by SEM and X‐ray Analysis. Issue 34 (28th October 2015) - Kulikov, Oleg V.; Siriwardane, Dumindika A.; McCandless, Gregory T.; Barnes, Charles; Sevryugina, Yulia V.; DeSousa, Joseph D.; Wu, Jingbo; Sommer, Roger; Novak, Bruce M.
Abstract: A small library of ureas and related compounds was synthesized and examined by scanning electron microscopy (SEM), single‐crystal X‐ray diffraction, powder X‐ray (pXRD), and polarized optical microscopy (POM) techniques in order to elucidate the factors controlling their self‐assembly in the solid state. Inspection of the 12 solid‐state structures revealed that molecules in the crystal lattice are held together by intermolecular H‐bonding, π–π stacking as well as C‐H/π interactions. The same interactions are likely responsible for the formation of supramolecular aggregates (e.g. sheet‐like assemblies, micro‐ and nano‐fibers, and the porous networks easily identifiable by SEM technique) and in certain cases led to the small molecules gelation. Abstract : Thorough structural analysis (X‐ray, pXRD, SEM) of a range of mono‐, bis‐ and tris‐ureas as well as thioureas has been performed in order to elucidate the factors controlling their self‐assembly properties in the solid state. Varying parameters such as structure, concentration, solvent, temperature, and deposition method would open up possibilities to tune supramolecular architectures (e.g., changing their shape and size through controlling non‐covalent interactions).